PERENCANAAN SISTEM PENYEDIA AIR BERSIH IKK KARANGBINANGUN - Sholeh Sholeh; Nur Azizah Affandy (Litbang Pemas - Universitas Islam Lamongan, 2017)
Water is a basic human need. The effect of water is vast for life, especially water for cooking and drinking. Karangbinangun district does not yet have a good and clean water supply network system. In the effort to provide clean water, distribution network is important. Because this distribution network that distributes from production installation to the community. The purpose of this research is to know the planning of clean and good network system for Karangbinangun district and To know the average amount of water demand needed by the people of Karangbinangun district in the next 10 (ten) years. The research methods using two methods, namely data collection technique, and data analysis technique. Data collection technique was conducted with primary survey and secondary survey. As for data analysis processed using the relevant empirical formula, without changing the authenticity of data. Prediction of population In Karangbinangun district in 2026 is 17420. And from the calculation of planning can be known service of clean water requirement in Karangbinangun district in year projection 2026 minimum required debit is 1,443,818,38 lt / hr or 60,159,10 lt / jm = 1,002.65 lt / mnt = 16,71 lt / dt = 0.02 m3 / s. From the calculation result is known pipe diameter of 150 mm, and pump spesification Q = 16,71 lt / dt and Head of 27,9 m or 30 m, for planning of water supply system IKK Karangbinangun.